Plan A, Plan B, and Plan C-OVID-19: adaptations for fly-in and fly-out mental health providers during COVID-19. Issue 1 (1st January 2021) - Roberts, Candace; Darroch, Francine; Giles, Audrey; van Bruggen, Rianne
ABSTRACT: Mental health providers have rapidly pivoted their in-person practices to teletherapy and telehealth interventions to address the increased demand for mental health services during the COVID-19 crisis. The change to service delivery has emphasised challenges for mental health service providers, particularly in regions that rely on fly-in and fly-out (FIFO) mental health service providers who are no longer able to travel to their places of work. In this qualitative study, we examined the impact of COVID-19 on the delivery of mental health services in Inuit Nunangat. Using a participatory action research methodology, we conducted semi-structured interviews with eight FIFO mental health service providers to understand their experiences and implement strategies to effectively deliver mental health services in a pandemic. We identified three themes through thematic analysis: 1) Service providers identify the challenges in adapting their practices to meet individual and community needs; 2) Service providers recognise the opportunities for enhancements to service delivery; 3) Service providers identify telemental health services as a potentially effective adjunct to in-person sessions. The findings support reconceptualising post-pandemic mental health service delivery to include both face-to-face and telemental health services.